Enhancing Students’ Argumentation Skill Using an Argument Driven Inquiry-Based Module - Shinta Devi Amielia; Suciati Suciati; Maridi Maridi (Intelektual Pustaka Media Utama, 2018)
Argumentation skills as a form of communication to externalize ideas through scientific discourse is a very important in learning of science. As an integral part of the science, argumentation skills should be integrated as a component of learning science. The purpose of this study is to determine the effectiveness of argument driven inquiry-based module in enhanching the students’ argumentation skills. This study was conducted at one of the State Senior High School in Surakarta academic year 2016/2017. The pre-test and post-test research pattern with treatment and control class groups were used throughout the study. While the treatment group taught by using module based on argument-driven inquiry, the control group was taught by a module that commonly used in the school. As the study concluded, using argument driven inquiry-based module in the learning process is effective to enhance the quality of students’ argumentation skills.